Dimensional regularization and renormalization of non-commutative quantum field theory - Gurǎu, Rǎzvan; Tanasa, Adrian (Annales Henri Poincaré, 2008)
Using the recently introduced parametric representation of noncommutative quantum field theory, we implement here the dimensional regularization and renormalization of the vulcanized $$Φ^{*4}_{4}$$model on the Moyal space.